Multi-institutional, prospective, observational study comparing the Gastrografin challenge versus standard treatment in adhesive small bowel obstruction. Issue 1 (July 2017) - Zielinski, Martin D.; Haddad, Nadeem N.; Cullinane, Daniel C.; Inaba, Kenji; Yeh, Dante D.; Wydo, Salina; Turay, David; Pakula, Andrea; Duane, Therese M.; Watras, Jill; Widom, Kenneth A.; Cull, John; et al.
Abstract : INTRODUCTION: Existing trials studying the use of Gastrografin for management of adhesive small bowel obstruction (SBO) are limited by methodological flaws and small sample sizes. We compared institutional protocols with and without Gastrografin (GG), hypothesizing that a SBO management protocol utilizing GG is associated with lesser rates of exploration, shorter length of stay, and fewer complications. METHODS: A multi-institutional, prospective, observational study was performed on patients appropriate for GG with adhesive SBO. Exclusion criteria were internal/external hernia, signs of strangulation, history of abdominal/pelvic malignancy, or exploration within the past 6 weeks. Patients receiving GG were compared to patients receiving standard care without GG. RESULTS: Overall, 316 patients were included (58 ± 18 years; 53% male). There were 173 (55%) patients in the GG group (of whom 118 [75%] successfully passed) and 143 patients in the non-GG group. There were no differences in duration of obstipation (1.6 vs. 1.9 days, p = 0.77) or small bowel feces sign (32.9% vs. 25.0%, p = 0.14). Fewer patients in the GG protocol cohort had mesenteric edema on CT (16.3% vs. 29.9%; p = 0.009). There was a lower rate of bowel resection (6.9% vs. 21.0%, p < 0.001) and exploration rate in the GG group (20.8% vs. 44.1%, p < 0.0001). GG patients had a shorter duration of hospital stay (4 IQR 2–7 vs. 5 days IQR 2–12; p = 0.036) and a similar rate of complications (12.5% vs. 17.9%; p = 0.20). Multivariable analysis revealed that GG was independently associated with successful nonoperative management. CONCLUSION: Patients receiving Gastrografin for adhesive SBO had lower rates of exploration and shorter hospital length of stay compared to patients who did not receive GG. Adequately powered and well-designed randomized trials are required to confirm these findings and establish causality. LEVEL OF EVIDENCE: Therapeutic, level III.